Perspectives on Low Temperature Tolerance and Vernalization Sensitivity in Barley: Prospects for Facultative Growth Habit - Muñoz-Amatriaín, María; Hernandez, Javier; Herb, Dustin; Baenziger, P. Stephen; Bochard, Anne Marie; Capettini, Flavio; Casas, Ana; Cuesta-Marcos, Alfonso; Einfeldt, Claus; Fisk, Scott; Genty, Amelie; Helgerson, Laura; et al. (Frontiers in Plant Science, 2020)
One option to achieving greater resiliency for barley production in the face of climate change is to explore the potential of winter and facultative growth habits: for both types, low temperature tolerance (LTT) and vernalization sensitivity are key traits. Sensitivity to short day photoperiod is a desirable attribute for facultative types. In order to broaden our understanding of the genetics of these phenotypes, we mapped QTLs and identified candidate genes using a GWAS panel comprised of 882 barley accessions that was genotyped with the Illumina 9K SNP chip. Fifteen loci including five known and ten novel QTL/genes were identified for LTT - assessed as winter survival in ten field tests and mapped using a GWAS meta-analysis. FR-H1, FR-H2 and FR-H3 were major drivers of LTT, and candidate genes were identified for FR-H3. The principal determinants of vernalization sensitivity were VRN-H1, VRN-H2, and PPD-H1. VRN-H2 deletions conferred insensitive or intermediate sensitivity to vernalization. A subset of accessions with maximum LTT were identified as a resource for allele mining and further characterization. Facultative types comprised a small portion of the GWAS panel but may be useful for developing germplasm with this growth habit.